Human Resources Management in Social Network Content Moderation: Perspectives from the Digital Services Act - Núñez Cansado, Marian; Quintana Gómez, Ángel (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2026)
This study evaluates the implementation of human resources in content moderation in large digital platforms (VLOPs) within the European Union, using a quantitative methodology based on documentary and data analysis. The results show significant disparities in the ratio of moderators per language, with TikTok and YouTube leading in coverage, while LinkedIn and X present critical gaps. It is concluded that, although the platforms comply with regulatory dictates, the lack of full language coverage and inadequate working conditions pose significant risks to vulnerable communities and moderators.